Effects of Searching for Street Parking on Driver Behaviour and Physiology: Results From an On-Road Instrumented Vehicle Study. (September 2018) - Ponnambalam, Canmanie Teresa; Cheng, Ryan; Donmez, Birsen
Studies regarding street parking have identified safety concerns due to the presence of parked cars, reduced road width, increased and erratic traffic flow, and reduced line of sight. However, few parking-related studies have focused on drivers searching for parking, an often-necessary task that may be considered stressful. An on-road instrumented vehicle study was conducted in an urban environment to assess the effects of searching for parking on driver behaviour and physiology. Twenty-eight participants drove two routes: one with a parking-search task and the other without (baseline condition). When searching for parking, drivers had a significant reduction in their speed, drove closer to the curb and indicated a higher self-reported workload. In addition, there were results approaching significance of increased heart rate and decreased variation in lane position. Further research is needed to determine the potential safety implications of these effects caused by searching for street parking.